Is injury associated with team performance in elite Australian football? 20 years of player injury and team performance data that include measures of individual player value - Hoffman, D. T.; Dwyer, D. B.; Bowe, S. J.; Clifton, P.; Gastin, P. B. (British Journal of Sports Medicine, 2020)
OBJECTIVES: To determine whether specific injury measures were associated with team performance in the Australian Football League (AFL). METHODS: 15.289 injuries caused players from 18 teams to miss 51.331 matches between 1997 and 2016. Data were aggregated to the team level. We analysed the associations among injury measures and team performance (reaching finals/playoffs and specific ladder/table position). Injury measures per team included: injury incidence, injury severity, injury burden, player match availability and percentage of the full player roster injured. We also weighted injury measures by five measures of player value. RESULTS: AFL teams' injury burden and player match availability were associated with final table position (r2=0.03, p<0.05). Player value weighted injury burden was different between finalists and non-finalists (mean difference=-8, p<0.001) and explained 12% of the variation in the table position of teams (p<0.001). For a team, nine missed matches due to injury (burden weighted by a best and fairest player rating system) was associated with one lower table position. Player match availability weighted by player value was higher for finalists than non-finalists (mean difference=1.7, p<0.01) and explained 7% of the variation in the table position of teams (p<0.001). DISCUSSION AND POTENTIAL IMPLICATIONS: The impact of injury (burden weighted by best and fairest) explained up to 12% of the variation in final table position-this is particularly relevant to making/not making playoffs as well as home ground/travel advantages for those teams that make the one-game format of AFL playoffs (not home-away or best of seven format).